Model of Ecotourism Management in Small Islands of Bunaken National Park, North Sulawesi - Tangian, Diane; Djokosetiyanto, Daniel; Kholil, Kholil; Munandar, Aris (Graduate School, Universitas Brawijaya, 2015)
The Bunaken National Park is one of the famous national park for tourism in North Sulawesi, Indonesia. The abundance natural resources is one of the crucial natural attraction for tourism in Bunaken. Tourism in Bunaken contributes significantly in local economic development. In the same situation, however, tourism contributes negatively to environment. Tourist activities contributes significantly in coral reef covers. Utilization of natural resources as an object and attraction needs to be done carefully, taking into account the balance of ecological, socio-economic and socio-cultural. The concept of ecotourism with three aspects of development were important in aspect in Bunaken National Park tourism development. The management of the park tour needs to be done based on the concept and principles of ecotourism. The Bunaken National Park tourist management model simulated by the dynamic system with the Powersim Constructor software show the number of tourist 2035 reached 27,152.98, extensive coral cover 447.87ha, the local community incomes Rp 15,834,861,419.63 and government revenues Rp 1,751,770,691.04. Keywords: conservation area, ecotourism, powersim model, sustainable management.